Dialogic Education in Spain: Some Initial Words - Marta Soler-Gallart (Networks: An Online Journal for Teacher Research, 2004)
In April 2003 three educational conferences were organized simultaneously in three different Spanish cities Barcelona, Zaragoza and Vitoria under the title "Learning Communities: Quality Education for All". These conferences meant the celebration of the success and consolidation of an educational project that has been taking place in Spain since the beginning of the nineties and that each year continues to expand throughout the country. All the schools that function as Learning Communities have a feature in common: they are based on dialogic learning and they are oriented towards achieving school success for all children. Both Gordon Wells and Marta Soler-Gallart participated in the conference: Gordon was invited to share his ideas on dialogic inquiry and to describe his experiences and research in schools; Marta explained the theory and practice of dialogic literacy drawing on her experience with teachers in some of the learning communities.